2019
DOI: 10.1111/andr.12721
|View full text |Cite
|
Sign up to set email alerts
|

Redox status assessment in infertile patients with non‐obstructive azoospermia undergoing testicular sperm extraction: A prospective study

Abstract: Background Oxidative stress (OS) is one of the most prevalent causes of sperm damage, through the toxic effects of endogenously generated hydrogen peroxide, superoxide anion, and hydroxyl radicals. Peripheral leukocytes represent a feasible model for studying the pathophysiology of OS‐mediated homeostasis, which can be responsible for cell dysfunction and cell injury. Objective To evaluate the redox status in patients with non‐obstructive azoospermia (NOA), establishing the potential role exerted by reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
4
23
1
Order By: Relevance
“…Indeed, DNA breaks and oxidative stress induced by impaired chromatin compaction could be the major reasons of poor semen morphology. 22,23 However, although in c-ICSI cycles the embryologists aim to select an ideal spermatozoa at 400x-power magnification, relying on normal morphology, the percentage of spermatozoa with high DNA fragmentation could be greater than 55%, even in the amount of morphologically normal ones. 24,25 This could be one reason why, in our series, worst sperm morphology is related to lower fertilization rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DNA breaks and oxidative stress induced by impaired chromatin compaction could be the major reasons of poor semen morphology. 22,23 However, although in c-ICSI cycles the embryologists aim to select an ideal spermatozoa at 400x-power magnification, relying on normal morphology, the percentage of spermatozoa with high DNA fragmentation could be greater than 55%, even in the amount of morphologically normal ones. 24,25 This could be one reason why, in our series, worst sperm morphology is related to lower fertilization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, morphology defects in the spermatozoa seem to be positively correlated with fragmented DNA both in whole semen and single retrieved cells. Indeed, DNA breaks and oxidative stress induced by impaired chromatin compaction could be the major reasons of poor semen morphology 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Cito et al revealed that the reactive oxygen species (ROS) production of NOA was significantly higher than that of normozoospermic men, and it may be related to spermatogenesis disorders in NOA patients [ 13 ]. Vatannejad et al published a study revealing that ROS also damage sperm nuclear DNA, displaying a negative effect on sperm DNA fragmentation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated concentrations of macrophages and sperm fragments in the distal epididymis may affect the sperm quality [17]. Moreover, according to previous authors, higher levels of reactive oxygen species and sperm DNA fragmentation could mediate the reproductive toxicity [18]. In our patients, the presence of high levels of polyunsaturated fatty acids on the sperm membrane; the low quantities of glutathione peroxidase, superoxide dismutase, and cytoplasm; and the presence of inactive, highly condensed chromatin could have led to a reduction in fertilization competence, motility, and viability, as well as a loss of DNA repair capacity [19].…”
Section: B Amentioning
confidence: 91%